Driving sustainability in the green entrepreneurial intentions among SMEs in the Electric vehicle component industry - Kongling Zhao; Annamalah Sanmugam; Kalisri Logeswaran Aravindan (Discover Sustainability)
Abstract Sustainable development has elevated the role of green entrepreneurship, notably in China's electric vehicle (EV) components sector, which presents vast opportunities for SMEs. While studies have explored the success and failure of Green Entrepreneurial Intention, factors influencing it remain under-researched, particularly from the perspective of individual intentions. Existing research primarily focuses on policies, regulations, and macro-environments affecting green business models, with limited attention to influence entrepreneurial and sustainable initiatives. This study aims to bridge this gap by examining the impact of Perceived Attitude, Perceived Behavioural Control, Subjective Norms, and Organizational Commitment on Green Entrepreneurship Intention, using Openness to Experience as a moderating factor. Data were collected through a cross-sectional survey from 383 SMEs in China, employing a simple random sampling technique. PLS-SEM regression analysis was used to test the hypotheses, guided by the Theory of Planned Behaviour (TPB) and Organizational Commitment (OC) theory. The findings revealed that Perceived Attitude significantly and positively influences green entrepreneurship intentions. Highly integrative subjective norms were also positively correlated with green entrepreneurship intentions. Furthermore, Perceived Behavioural Control and Organizational Commitment facilitated green entrepreneurship intentions. Openness to Experience emerged as a strong moderator in the relationships between Perceived Attitude and Subjective Norms with Green Entrepreneurship Intention. This study contributes to the existing knowledge base by highlighting the gaps and inconsistencies in the literature regarding TPB and OC factors influencing green entrepreneurship intention. The results have theoretical and managerial implications, emphasizing the importance of fostering green entrepreneurship.